A Comprehensive Analysis of STEAM Learning Implementation to Foster Critical Thinking Skills for Equitable and Quality Physics Education in High Schools - Lailatul Fajriati; Hanan Zaki Alhusni; Rahmatta Thoriq Lintangesukmanjaya (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: The objective of this study is to examine the implementation of STEAM learning in enhancing the critical thinking skills of high school students in Physics, particularly in Indonesia. Method: The methodology consists of a literature review, which involves identifying and evaluating articles or journals related to STEAM learning and its impact on students’ critical thinking in Physics. Through a systematic screening process, the initial 40 articles were narrowed down to 30, and ultimately, 20 articles were selected for detailed review. Results: The findings reveal that the application of STEAM learning has a significant positive effect on the critical thinking abilities of high school students with respect to Physics. Novelty: This approach aligns with global and national initiatives such as the Sustainable Development Goals (SDGs), highlighting the need for innovative educational programs that address contemporary challenges. In the 21st century, critical thinking, analytical skills, and creativity are essential. STEAM education—integrating science, technology, engineering, arts, and mathematics—serves as an effective strategy to equip students for future demands in education and beyond.